Consumptive Behavior in Makeup Product Purchases among University Students: The Role of Self-Control, Peer Conformity, and Electronic Word of Mouth - Alvita Dewi Maharani; Istiqlaliyah Muflikhati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2025)
Female university students generally have the potential to spend up to half of their monthly allowance on beauty-related products. Of this amount, approximately 30 percent may be specifically allocated to makeup needs. Excessive and need-exceeding purchasing habits of makeup products among female students can lead to financial inefficiency, thereby fostering consumptive behavior. This study employed a quantitative approach with a cross-sectional research design. The sampling technique used was non-probability sampling, specifically voluntary sampling. A total of 217 female students participated as respondents in this study. The results of the correlation analysis indicate that female students from faculties with a social science orientation, such as the Faculty of Human Ecology, the Faculty of Economics and Management, and the School of Business, tend to exhibit higher levels of consumptive behavior in purchasing makeup products. Furthermore, female students with higher monthly allowances tend to have lower levels of self-control and higher levels of consumptive behavior related to makeup purchases. The results of the influence analysis reveal that consumptive behavior in makeup product purchases among female students is significantly influenced by negative self-control and positive peer conformity. Therefore, female students are encouraged to enhance their self-control in order to avoid tendencies toward consumptive behavior.